Preservation of Ejaculatory Function After Postchemotherapy Retroperitoneal Lymph Node Dissection (PC-RPLND) in Patients With Testicular Cancer: Template vs. Bilateral Resection - Hiester, Andreas; Nini, Alessandro; Fingerhut, Anna; große Siemer, Robert; Winter, Christian; Albers, Peter; Lusch, Achim (Frontiers in Surgery, 2019)
Background To evaluate the functional outcome regarding the preservation of ejaculatory function comparing a bilateral versus unilateral template resection in PC-RPLND patients. In addition, oncological safety and perioperative complications of the unilateral template resection was compared to the full bilateral one. Material&Methods Between 2003 and 2018, 504 RPLNDs have been performed in 434 patients. The database of consecutive patients was queried to identify 171 patients with PC-RPLND after 1st line chemotherapy for a non-seminoma with or without bilateral template resection. Indication for template resection was a unilateral residual mass mainly less than 5cm. Descriptive statistics were used to report preoperative features, postoperative outcomes and patterns of recurrence, on the overall population and after stratification for the type of resection (bilateral vs. unilateral). Kaplan-Meier analyses were used to describe recurrence- and cancer-specific mortality-free survival rates at different time points. Results Overall, 90 and 81 patients underwent unilateral and bilateral radical resection, respectively. Median size of residual mass was 7cm for bilateral and 4cm for unilateral template resection. Clinical stage II and III were present in 31% and 69% of patients, respectively. Median follow-up was 14.5 months. The 1-and 2-year recurrence-free survival rates were 91% and 91%, and 77% and 72% for unilateral template and bilateral resection, respectively (p=0.0078). Median time to recurrence was 9.5 and 9 months in template and bilateral resection group, respectively. Adjunctive procedures were performed in 56 patients (33%) and were significantly more frequent in bilateral resection group (43%vs.23%, p=0.006). The overall high-grade complication rate (Clavien-Dindo ≥III) was 6%, 3% and 9% in unilateral template and bilateral resection group, respectively (p=0.6). The rate of preservation of antegrade ejaculation was significantly higher in the unilateral group Conclusions Unilateral template resection is oncologically safe in terms of mid-term recurrence and CSM-free survival rates for patients with a residual mass less than 5 cm. This data undermines the growing evidence of limited PC-RPLND being justifiable in strictly unilateral residual mass < 5 cm. Antegrade ejaculation can be preserved at a much higher rate without increasing the mid-term recurrence rate. This data has to be confirmed with a longer follow-up.